Antioxidant and antimicrobial activity of bacteriocin-producing strains of lactic acid bacteria isolated from the human gastrointestinal tract - Prosekov, Alexander Yurievich; Dyshlyuk, Lyubov Sergeevna; Milentieva, Irina Sergeevna; Sykhikh, Stanislav Alekseevich; Babich, Olga Olegovna; Ivanova, Svetlana Anatolievna; Pavsky, Valery Alekseevich; Shishin, Mikhail Vladimirovich; Matskova, Ludmila Valentinovna (Progress in Nutrition, 2017)
Background: cancer patients require special attention to maintenance therapy of their organism vital activity. Distribution of nutritional deficiency in cancer patients not only limits the possibilities of application of modern treatment methods, but can also be the direct cause of life-threatening complications and premature death. Objective: to study the use of bioactive peptide complexes with low molecular weight and probiotic strains isolated from the human gastrointestinal tract in food products intended for patients with cancer during their treatment and rehabilitation. Material and Methods: 14 strains of lactic acid bacteria were pre-selected and identified for this study. They were allocated from the gastrointestinal tract of 500 healthy people and people with cancer, who presented different age groups. The study of antagonistic activity of lactic acid bacteria was carried out by using the MRS medium and Lysogeny broth (LB). Biocompatibility study was performed through the co-culture method on solid MRS medium. Results: Research results proved that the isolated metabolites belonged to bacteriocins, as the studied microorganisms were resistant both to their inhibitors and mutually resistant to the single-type synthesized substances. Conclusions. Probiotics have a positive effect on the immune system, as the gastro-intestinal flora they reduce the impact of mutagens and carcinogens.